Hubungan Perkembangan Kognitif dan Perkembangan Motorik Halus Anak Usia 5-6 Tahun Menggunakan Media Loose Parts - Purbayani, Rini; Ali, Nabila Nurhaliza (JOECE: Journal of Early Childhood Education, 2025)
This study aims to investigate the relationship between cognitive development and fine motor development in children aged 5–6 years, utilizing loose parts media. The study used a correlational quantitative approach with 10 children as subjects. Data were collected using a validated Likert scale questionnaire and analyzed using Spearman's correlation test with the help of SPSS version 25. The results showed that most of the children's cognitive development fell into the "Developing as Expected" category (80%), followed by "Developing Very Well" (10%) and "Beginning to Develop" (10%). The children's fine motor development showed good results, with 60% of children in the Developing as Expected category and 40% in the Developing Very Well category. However, the correlation test results showed a significance value of 0.596 (>0.05) with a correlation coefficient of 0.191, indicating no significant relationship between cognitive and fine motor development. Thus, the use of loose parts media has not been statistically proven to show a correlation between these two aspects of development.